2017
DOI: 10.1097/cej.0000000000000218
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic blockers and the risk for common solid cancers: a case–control study

Abstract: Laboratory studies have suggested that adrenergic blockers may inhibit the proliferation and migration of cancer cells, but epidemiological evidence of their effect on cancer incidence has proven inconsistent. We therefore conducted a case-control study using the Clinical Practice Research Datalink to assess the effect of adrenergic blockers on the incidence of prostate, lung, bowel and breast cancers. From among patients aged 18 years or older who contributed at least 2 years of prospectively gathered data be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Our conclusion that BBs were associated with increased breast cancer risk was consistent with this highly influential and large studies ( Numbere et al, 2015 ; Chang et al, 2016 ; Zheng et al, 2021 ). The prospective study data minimizes the recall bias and in the study in question, some important confounders such as alcohol status, smoking status, BMI, medication and comorbidities, were adjusted.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our conclusion that BBs were associated with increased breast cancer risk was consistent with this highly influential and large studies ( Numbere et al, 2015 ; Chang et al, 2016 ; Zheng et al, 2021 ). The prospective study data minimizes the recall bias and in the study in question, some important confounders such as alcohol status, smoking status, BMI, medication and comorbidities, were adjusted.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 842 potentially eligible studies were retrieved from the selected databases during the initial search. After removing duplicates and further screening the titles and abstracts, 26 studies on breast cancer risk ( Meier et al, 2000 ; Li et al, 2003 ; Gonzalez-Perez et al, 2004 ; Fryzek et al, 2006 ; Largent et al, 2006 ; Davis and Mirick, 2007 ; Van Der Knaap et al, 2008 ; Coogan et al, 2009 ; Largent et al, 2010 ; Huang et al, 2011 ; Hallas et al, 2012 ; Lee et al, 2012 ; Mackenzie et al, 2012 ; Biggar et al, 2013 ; Li et al, 2013 ; Saltzman et al, 2013 ; Devore et al, 2015 ; Numbere et al, 2015 ; Azoulay et al, 2016 ; Chang et al, 2016 ; Gomez-Acebo et al, 2016 ; Wilson et al, 2016 ; Brasky et al, 2017 ; Raebel et al, 2017 ; Busby et al, 2018b ; Zheng et al, 2021 ), and 30 studies on breast cancer prognosis ( Powe et al, 2010 ; Barron et al, 2011 ; Ganz et al, 2011 ; Melhem-Bertrandt et al, 2011 ; Shah et al, 2011 ; Şendur et al, 2012 ; Holmes et al, 2013a ; Holmes et al, 2013b ; Botteri et al, 2013 ; Cardwell et al, 2013 ; Chae et al, 2013 ; Sorensen et al, 2013 ; Boudreau et al, 2014 ; Cardwell et al, 2014 ; Sakellakis et al, 2014 ; Babacan et al, 2015 ; Chen et al, 2015 ; Springate et al, 2015 ; Cardwell et al, 2016 ; Choy et al, 2016 ; Chen et al, 2017 ; Spera et al, 2017 ; Busby et al, 2018a ; Musselman et al, 2018 ; Cui et al, 2019 ; Takada et al, 2019 ; Modi et al, 2...…”
Section: Resultsmentioning
confidence: 99%
“…Studies were retrieved by filtering titles and abstracts, and 39 studies were excluded after full text review, and reasons why studies were excluded were listed in Supplementary Table S4 . Ultimately, we included 37 studies for our meta-analysis, including 20 publications concerning cancer risk ( Pahor et al, 1996 ; Michels et al, 1998 ; Rosenberg et al, 1998 ; Tenenbaum et al, 2001 ; Beiderbeck-Noll et al, 2003 ; Boudreau et al, 2008 ; van der Knaap et al, 2008 ; Friedman et al, 2011 ; Hallas et al, 2012 ; Jansen et al, 2012 ; Wang et al, 2012 ; Mansouri et al, 2013 ; Makar et al, 2014 ; Chang et al, 2015 ; Lin et al, 2015 ; Numbere et al, 2015 ; Grimaldi-Bensouda et al, 2016 ; Dierssen-Sotos et al, 2017 ; Cheung et al, 2020 ; Brasky et al, 2021 ), 17 regarding cancer prognosis ( Sorensen et al, 2000 ; Hicks et al, 2013 ; Holmes et al, 2013 ; Cardwell et al, 2014 ; Jansen et al, 2014 ; Giampieri et al, 2015 ; Osumi et al, 2015 ; Morris et al, 2016 ; Jansen et al, 2017 ; Weberpals et al, 2017 ; Sud et al, 2018 ; Bowles et al, 2019 ; Cui et al, 2019 ; Fiala et al, 2019 ; Mafiana et al, 2019 ; Ozawa et al, 2019 ; Ahl et al, 2020 ). Of these 37 studies, 26 studies used cohort design, three studies used nested case-control design, and 8 studies used case-control design.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, other studies conclude that the use of β-blockers has no effect on the prognosis or survival of patients with breast cancer [17,30]. Furthermore, other retrospective studies associated the use of β-blockers with an increased risk of breast cancer and recurrence rates [19]. All these works demonstrate inconsistencies related to the use of β-blockers and their specific role in the breast.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have suggested that β-adrenergic antagonists can inhibit multiple cellular processes, including cell proliferation and metastases [16]. However, the evidence regarding the effect of β-blockers on the breast is so far contradictory, showing inconsistencies related to the use of β-blockers and their specific role [17][18][19][20]. The similarity of action found between agonists and antagonists can be explained by the fact that several β-adrenergic antagonists do not really act as pure antagonists [21].…”
Section: Introductionmentioning
confidence: 99%